2018
DOI: 10.1371/journal.pone.0198568
|View full text |Cite
|
Sign up to set email alerts
|

Long term trends and spatial distribution of animal bite injuries and deaths due to human rabies infection in Uganda, 2001-2015

Abstract: BackgroundIn the absence of accurate data on trends and the burden of human rabies infection in developing countries, animal bite injuries provide useful information to bridge that gap. Rabies is one of the most deadly infectious diseases, with a case fatality rate approaching 100%. Despite availability of effective prevention and control strategies, rabies still kills 50,000 to 60,000 people worldwide annually, the majority of whom are in the developing world. We describe trends and geographical distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 23 publications
2
67
0
Order By: Relevance
“…The results of this study showed that the incidence of animal bites in the Najaf Abad has been increased; in this survey, the average incidence of animal bites in Najaf Abad per 100,000 people has increased from 204.46 in 2012 to 219.98 in 2017. A Ugandan study also founded an elevating shift to study the long-term trends in the incidence of animal biting and deaths from 2001 to 2015 [20]. A study in Bhutan for the purpose of the occurrence of prophylaxis after exposure from 2005 to 2008 also confirms the increase in the incidence of animal bites [21].…”
Section: Discussionmentioning
confidence: 91%
“…The results of this study showed that the incidence of animal bites in the Najaf Abad has been increased; in this survey, the average incidence of animal bites in Najaf Abad per 100,000 people has increased from 204.46 in 2012 to 219.98 in 2017. A Ugandan study also founded an elevating shift to study the long-term trends in the incidence of animal biting and deaths from 2001 to 2015 [20]. A study in Bhutan for the purpose of the occurrence of prophylaxis after exposure from 2005 to 2008 also confirms the increase in the incidence of animal bites [21].…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have also shown that passive surveillance for rabies results in underreporting (19), particularly in developing countries (20,21). Analysis of ESD rabies surveillance data from 2001-2015 found that animal bites were increasing in Uganda (14), and it is reasonable to assume that complete reporting in NADDEC might have shown a similar trend. A full evaluation of both rabies surveillance systems and the challenges to complete reporting is important to enable the system to contribute to its fullest extent in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance data of animal bites among humans provides vital information to guide resource allocation in the control and prevention of rabies (13). An analysis of human rabies surveillance data from the Epidemiology and Surveillance Division (ESD) of the Ministry of Health in 2001-2015 in Uganda revealed 208,720 animal bites, with 486 suspected human rabies deaths (14). However, Uganda also captures rabies-related data in a veterinary surveillance system, at National Animal Disease Diagnostic Epidemiology Centre (NADDEC).…”
Section: Introductionmentioning
confidence: 99%
“…Animal bite of humans provides an important source of epidemiological information which is crucial in enhancing rabies surveillance in humans and animals [1]. Animal bite injury is a serious public health problem and an economic burden especially in developing countries where canine rabies vaccination coverage is very low [2].…”
Section: Introductionmentioning
confidence: 99%